Social Intelligence Dimensions and Secondary School Students’ Interest in Learning Biology - Izunna Nwuba; Josephine Nwanneka Okoli (Universal Education Jurnal Teaching and Learning, 2025)
The ongoing effort to identify variables that could be influenced for academic gains in the 21st-century classroom fueled the study on the predictive influence of social intelligence (SI) on secondary school students’ interest in Biology, applying a predictive correlational research design. 1,198 Secondary School Year 2 (SS2) students, obtained using a multistage sampling procedure, were the respondents. Two adapted instruments, the Social Intelligence Scale (SIS) and the Biology Interest Scale (BIS), were employed for data collection. The adapted instruments (SIS and BIS), validated by three experts, when pilot tested, gave reliability coefficient values of 0.79 and 0.86, established using Cronbach's alpha. The data collected were analyzed using simple and multiple linear regression analyses. The findings revealed, among others, that SI caused 20.1% variance in students’ interest in Biology, indicating that SI significantly and positively contributed to students' interest in Biology. On relative contributions of individual dimensions of SI, the study also revealed that all the dimensions of SI, individually and jointly, significantly predicted students’ interest in biology. Based on the findings, it was recommended among others that education stakeholders should organize periodic trainings, sensitization and orientation programmes to educate students on strategies that can be adopted to promote the acquisition of social intelligence skills.